Analisis Efisiensi Operasional Syariah Dalam Industri Perhotelan : Pendekatan Manajemen Operasional Syariah Pada Proses Check-In Dan Check-Out - Mhd Dimas Jayadi; Chuzaimah Batubara (Universitas Katolik Widya Karya Malang, 2023)
This study aims to analyze the efficiency of sharia operations in the hotel industry by using sharia operational management approach in the check-in and check-out process. Operational efficiency is a key factor in the success of a hospitality business, and with the Islamic operational management approach, aspects of sharia are also integrated into operational processes.The research method used in this study is descriptive analysis by collecting data from various sources, including literature studies, field observations, and interviews with hotel managers who apply Islamic operational principles. The collected data was analyzed using a qualitative approach to gain deep insight into the operational efficiency of Sharia. The results of the analysis show that the application of sharia operational management in the check-in and check-out process can improve operational efficiency in the hotel industry. Some of the measures taken include the use of technology to speed up the check-in process, staff training in terms of friendly and efficient service in accordance with sharia principles, and the implementation of policies that promote integrity and transparency.In conclusion, the Islamic operational management approach can provide great benefits for the hotel industry in achieving operational efficiency. By paying attention to sharia aspects in the check-in and check-out process, the hotel can meet the needs of guests who want services that are in accordance with sharia values. In addition, the use of technology and proper staff training also play an important role in improving overall operational efficiency.